SURGICAL CANDIDACY OR WEIGHT STIGMA? THE DILEMMA OF OBESE PATIENTS IN ORTHOPAEDICS – A SYSTEMATIC REVIEW OF THE LITERATURE - Aleksandra Borowy; Wiktoria Suchcicka; Aleksandra Chajnowska; Julia Guzowska; Patrycja Rzeźnik; Maciej Sobczyk; Weronika Stachera; Julia Stępień; Barbara Wołoszyn; Małgorzata Zach (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Obesity (BMI ≥ 30) is a rapidly growing global health issue with significant implications for orthopedic health. It contributes to joint degeneration and complicates surgical treatment through both biomechanical strain and systemic inflammation, particularly affecting the hip, knee, and upper extremities. Aim: This systematic review aims to evaluate the impact of obesity on orthopedic disorders and surgical outcomes and to assess the validity of excluding patients from surgery based solely on BMI criteria. State of Knowledge: Obesity significantly increases the risk of postoperative complications, including infections, reoperations, technical difficulties, and inferior functional recovery. Hip and knee arthroplasties in obese patients often yield less optimal results compared to non-obese individuals, though the overall benefit remains considerable. In the upper limbs, obesity is linked to poorer outcomes in rotator cuff repair and higher incidence of compression neuropathies. Despite these challenges, many obese patients report substantial improvements post-surgery. Denying surgery based solely on BMI is not consistently supported by current evidence and may exacerbate health inequalities. Bariatric surgery shows promise in mitigating some orthopedic complications and may improve outcomes. Conclusions: Obesity adversely affects surgical outcomes in orthopedics, but BMI should not be the sole determinant in surgical eligibility. A more individualized, evidence-based approach—emphasizing preoperative weight management and equitable access—is essential for optimal care and outcomes.